2013
DOI: 10.1186/1471-2458-13-215
|View full text |Cite
|
Sign up to set email alerts
|

Persistent household food insecurity, HIV, and maternal stress in Peri-Urban Ghana

Abstract: BackgroundThe mental health of caregivers has been shown to be important for improving HIV prevention and treatment. Household food insecurity affects hundreds of millions of individuals in Sub-Saharan Africa, a region that experiences a disproportionate burden of the HIV pandemic. Both maternal HIV diagnosis and household food insecurity may be linked with maternal stress. This in turn may lead to unhealthy coping behaviors. We examined the independent associations of HIV, persistent household food insecurity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 28 publications
1
52
1
Order By: Relevance
“…In women, the effect of food insecurity on HRQoL was larger than for men. Food insecurity affects millions of households in SSA [42] and women tend to play a larger role in domestic responsibilities in this region [43]. …”
Section: Discussionmentioning
confidence: 99%
“…In women, the effect of food insecurity on HRQoL was larger than for men. Food insecurity affects millions of households in SSA [42] and women tend to play a larger role in domestic responsibilities in this region [43]. …”
Section: Discussionmentioning
confidence: 99%
“…29 An earlier study conducted in the Manya Krobo district indicated that 10% of mothers experienced postnatal depression and 58% perceived that they had experienced stress. 12,30 Additionally, persistent food insecurity was independently associated with maternal stress (aOR: 3.5, 95% CI: 1.1, 11.1). 30 Thus, poor maternal mental health is a plausible pathway for the observed association in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…12,30 Additionally, persistent food insecurity was independently associated with maternal stress (aOR: 3.5, 95% CI: 1.1, 11.1). 30 Thus, poor maternal mental health is a plausible pathway for the observed association in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,23 HFI is a very stressful condition that has been consistently associated with mental health problems among women. 24 High stress levels are reflected in high stress hormone levels (e.g., cortisol) that may be responsible for increasing visceral adiposity, a well established risk factor for type 2 diabetes. High stress levels have also been linked with hypertension.…”
Section: Discussionmentioning
confidence: 99%